Paying with your personal data: the insensitivity of private information provision to asymmetric benefits - Bettina Rockenbach; Abdolkarim Sadrieh; Anne Schielke (Journal of the Economic Science Association, 2021)
Internet services are often free of charge but ask for customers' personal data in exchange for usage. We experimentally study whether the provision of information-based public goods is susceptible to restraint when contributions not only make contributors better off but also enable a non-contributing "big player" to acquire substantial profits. We show that the presence of the big player crowds out the willingness to provide neutral tokens, but no such effect is observed for the provision of private information. Hence, collecting anonymized personal data instead of monetary fees can be more profitable to service providers and create greater benefits for customers.
Keywords: C91; D03; D64; D82; H41; M31; 330; Information public good; Sharing information; Personal data; Asymmetric benefits; Internet service providers